The undergraduate History Course at Universidade do Estado do Rio Grande do Norte (UERN): institutionalization and first curricular structures (1967-1978): creation and first curricular structures (Revista de História da UEG (REVHIST), 2021)
This article aims to analyze the creation and the first ten years of the undergraduate History course at the State University of Rio Grande do Norte (UERN), Mossoró campus (1967-1978). As historical sources, we work with the curricular structures, legislation internal to the said course and university, as well as MEC’s, teachers' point books and minutes book from the former Institute of Human Sciences (ICH). We interpret these sources by the references of curricular theories, which understand the organization of knowledge as socially situated, in time and space. Therefore, this allows us to understand the emergence of the History undergraduate course in the city in the midst of a series of initiatives that show the connection between a local political class and policies to promote culture, contributing to the history of the region's historiography and also to a methodological reflection on the field of history of higher education in history.Keywords: undergraduate History course. UERN. Mossoró. History of Historiography. Curriculum.